Spanish financial cooperative sector’s challenges facing systemic risk - Rubiño Box, José Antonio; Molina Moreno, Valentín (Cooperativismo & Desarrollo, 2018)
Purpose: The aim is to reflect on the Spanish financial cooperative sector based on the analysis of the concept, as well as on systemic risk typologies.Description: The business model proposed by credit cooperatives in Spain has strong foundations on orthodox financial culture in the sense that these entities, generally, have adopted financial sustainability as their strategic horizon.Point of view: Due to a given a series of regulatory procedures that have taken place in Spain, it is possible to affirm, in general terms, that, to a large extent, credit cooperatives have not been affected. This condition does not apply for savings banks, for example.Conclusions: In relation to the rest of entities and modalities that make up the banking system, credit cooperatives have less risk exposure, which affects the other institutions in the banking system. In addition, the great competitive advantage that these entities can count on will result from combining the provision of dimension, efficiency and financially sustainable services that face a convulsive future in coexistence with commercial banking entities that are increasingly competitive.
Keywords: Basel III; commercial banking; competitiveness; credit cooperatives; Spanish financial sector